Japanese Quality of Amae & Transience - Jhuma Basak (EJP import test, 2018)
Summary: The chief exposition of this paper attempts to explore (i) the Japanese concept of amae which indicates the dependency need of a child in the dyad that Takeo Doi explored extensively in his book The Anatomy of Dependence; and (ii) the quality of transience in human life-cycle interwoven with the evolutionary dynamic quality of amae working within it, which finds inquiry in the treatment of Osamu Kitayama’s works.
Keywords: Amae; Pre-oedipal; Transience; transition; Viewing-together